Dr. Radhakrishnan On The Dhammapada - R. , Subramony (International Journal of Psychosocial Rehabilitation, 2020)
In Gautama the Buddha we have a master mind from the East, second to none so far as the influence on the thought and life of the human race is concerned, and sacred to all as the founder of religious tradition whose hold is hardly less wide and deep than any other. Radhakrishnan further states that the Buddha belongs to the history of the world’s thought. He is part of the general inheritance of all cultivated men. He is undoubtedly one of the greatest figures in history.